Assessment of Shear Bond Strength to Sound and Artificial Caries Affected Dentin Using Different Adhesive Systems: An In Vitro Study - Zahraa Salman Al-Obaidi; Haider Hasan Jasim (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to determine how the various adhesive systems affect the shear bond strength (SBS) to normal and artificially create caries affected dentin (CAD) in permanent teeth. Methods: Forty eight sound premolars had their occlusal enamel ground to create flattened midcoronal dentin. According to the dentin substrate, specimens were allocated into sound and artificially created CAD induction using the pH-cycling technique. Each group was further subdivided according to the adhesive materials: Scotchbond Universal Plus, Scotchbond Universal, and Adper Single Bond 2 adhesives (applied in Etch and Rinse Adhesive Protocol). After that, a composite was put on and shear bond strength (SBS) tests were done. Data analyzed using two-way ANOVA and chi-squared tests. Results: Overall model test of the ANOVA statistics showed that both type of dentin and types of adhesive had a significant effect on the SBS values (P <  0.001). Tuckey post hoc comparisons showed a significant difference for type of dentin (P <  0.001) and types of adhesive (P ≤  0.005). Mode of failure assessment is non-statistically significant difference (P = 0.41). Conclusion: All adhesives showed a decrease in SBS when used on artificial CAD.